PERTANGGUNGJAWABAN HUKUM HAK GANTI RUGI BAGI KORBAN TINDAK PIDANA PENIPUAN MELALUI PENGGABUNGAN PERKARA BERDASARKAN KUHAP - Ilmi Luthfi Alfaris; Efa Laela Fakhriah (Iustitia Omnibus (Jurnal Ilmu Hukum), 2022)
ABSTRACT The settlement of criminal cases in Indonesia cannot only look at the fate of the perpetrators, but the victims who in this case suffer material and immaterial losses also need protection. Compensation is contained in civil law as well as in criminal law. This can only be found in formal criminal law, namely in Law Number 8 of 1981 concerning the Criminal Procedure Code. This study aims to analyze and understand the legal accountability of the right to compensation for victims of criminal acts of fraud through the merger of cases based on the Criminal Procedure Code and the discovery of obstacles in granting the right to compensation for victims of criminal acts of fraud through the merger of cases based on the Criminal Procedure Code. The approach method used in this research is normative juridical. The research specification in this thesis is descriptive analytical, with the data analysis used in writing the thesis is a qualitative analysis method. From the results of the analysis carried out, deductive conclusions are then drawn, which are described in narrative form without using formulas or statistical figures to then draw a specific conclusion. The results of the study concluded that the criminal act of fraud can obtain compensation for the crime that happened to it can be found in the Criminal Procedure Code, but in its implementation not all of them apply the case merger. Constraints that occur in the implementation of the merger of criminal cases include the compensation that can be decided is only limited to the reimbursement of costs that have been incurred by the injured party and the lack of public knowledge can also be caused by law enforcement officials who do not explain it to the victim to obtain their right to merge the lawsuit. compensation Keywords: Merger of Cases, Compensation, Criminal Procedure Code